Child Maltreatment, Mental Health Disorders, and Health Risk Behaviors in People With Diverse Gender Identities - Madzoska, Monica (Journal of interpersonal violence, 2025)
This study examined rates of mental health disorders and health risk behaviors in people with diverse gender identities and associations with five types of child maltreatment. We used data from the Australian Child Maltreatment Study (ACMS), a nationally representative survey of Australian residents aged 16 years and more, which was designed to understand the experience of child maltreatment (physical abuse, sexual abuse, emotional abuse, neglect, exposure to domestic violence). Mental disorders—major depressive disorder, generalized anxiety disorder (GAD), alcohol use disorder, post-traumatic stress disorder (PTSD), and health risk behaviors—smoking, binge drinking, cannabis dependence, self-harm, and suicide attempt in the past 12 months were assessed. People with diverse gender identities who experienced child maltreatment were significantly more likely to have GAD (43.3%; 95% CI [30.3, 56.2]) than those who had experienced child maltreatment who were either cisgender men (13.8%; [12.0, 15.5]) or cisgender women (17.4%; [15.7, 19.2]). Similarly, higher prevalence was found for PTSD (21.3%; [11.1, 31.5]), self-harm (27.8%; [17.1, 38.5]) and suicide attempt (7.2%; [3.1, 11.3]) for people with diverse gender identities. Trauma-informed approaches, attuned to the high likelihood of any child maltreatment, and the co-occurrence of different kinds may benefit people with diverse gender identities experiencing GAD, PTSD, self-harm, suicidal behaviors, or other health risk behaviors.